BUJANG DARA DALAM MEMPROMOSIKAN PARIWISATA DI KOTA PEKANBARU - ", Fitriani; Arief, Andi M Rifiyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Consideration of the author in using this method of qualitative methods are able to explain the phenomena through the collection of data obtained through interviews. Any data that can be processed and clearly defined using a language that is easily understood. This method does not use the sample population, because if the data collected has been profound and explain the phenomenon under study, it is not necessary to find other sampling. This study used a descriptive approach, where this research provides a detailed overview of the Dara Single Role In Promoting Tourism in the city of Pekanbaru. While data collection techniques in this research using techniques of observation, interviews and documentation. Based on the research that has been done, Single Dara has memepromosikan tourism in Pekanbaru. Promotion is done to help the development of tourism. Promotion of a tourist destination itself indispensable by areas that have potential. Keywords: Single Dara in promoting tourism in the city of Pekanbaru